Joanna Russ’s The Female Man: A Butlerian approach - Moslehi, Mahboubeh; Abbasi, Pyeaam (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
The present article focuses on Judith Butler’s theory of ‘gender performativity’ and its application to Joanna Russ’s science fiction, The Female Man (1975). Butler applies Foucault’s genealogical methodology in Gender Trouble (1999) to trace the processes by which identity is constructed within language and discourse. She sees the subject as the effect of institutions and discourses rather than the other way round, which implies that the subject cannot simply be but is always already instituted. She believes that since the subject is always involved in the endless process of becoming, it is possible to reassume or repeat subject hood in different ways. Butler’s genealogical critique of the category of the subject coincides with her notion that gendered and sexed identities are performative. She extends Beauvoir’s (1908-1986) famous statement that “one is not born, but rather becomes, a woman” and suggests that Beauvoir’s claim can be read as a formulation that shows gender as a process which has neither origin nor end, so that it is something that we ‘do’ rather than we ‘are’. Gendered identities are therefore performative i. e., based on repetition and since the repetitions which form the subject’s identity never finish, gender identity is never fixed. Russ (1937-2011) depicts four women from different worlds with different attributes which affirms Butler’s belief in performativity of gender that challenges the presumed fixed gender identities.